Evolution of the composting process with semi-permeable film technology at industrial scale. (1st March 2016) - González, Inmaculada; Robledo-Mahón, Tatiana; Silva-Castro, Gloria Andrea; Rodríguez-Calvo, Alfonso; Gutiérrez, M. Carmen; Martín, M. Ángeles; Chica, Arturo F.; Calvo, Concepción
Abstract: This study evaluated the composting process of a mixture of sewage sludge and bulking agent in a semi-closed system at industrial scale, which consisted of an aerated static windrow covered with a semi-permeable film. Physical-chemical and respirometric variables were studied and bacteria and fungi were monitored to assess the improvement in the composting process. The system was compared with conventional open windrows in which lengthy composting times are required to obtain stabilized compost, compost sanitation is not always reached and periodical turning must be carried out to avoid anaerobic conditions. The high temperatures reached and maintained during the stage under the semi-permeable film (≈80 °C) permitted the sanitation of the compostable substrate, as demonstrated by the rapid disappearance of Salmonella sp. and the decrease in Escherichia coli in only 5 days of the process. The total microorganism concentration also decreased during the composting process. The rapid decrease in carbon content expressed in volatile solids (VS) (around 41%) showed that the composting process carried out under the semi-permeable film could be shortened to 30 days. The evolution of thermophilic and mesophilic bacteria and fungi was conditioned by the windrow temperature and the biodegradable organic matter content. An adequate linear correlation (r 2  = 0.9214) between the total microorganism concentration (log CFU/g) and VS (%) was obtained during the composting process. Highlights: Composting was evaluated in a semi-closed system using semi-permeable film technology. Physical-chemical and microbiological variables were monitored and evaluated. The improvements achieved in comparison with an opened windrow system were evaluated. The composting process under semi-permeable film could be shortened to 30 days.